(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
This contribution examines the ceramic material found in the excavation of the Terme Milano (over 15000 fragments), analyzing the possibilities for study, research and reconstruction of the history of the site that these materials offer. This is mainly because of residual pottery, found out of context, primarily in stratigraphy and subsequent fills, and layers of abandonment that obliterates the great Baths complex in the south of the Praetorium. However, even these "rejected sherds" provide important information on the history and material culture of the site, showing stages of use or reuse of the thermal building, economic and social context of the town and offering interesting examples of products, both imported and locally produced, circulating at Gortys between the Roman and proto-byzantine ages.